Integrating Metabolic and Anatomical Imaging: Insights from FDG PET-CT in Brain Malignancies - Zohra, Fatema Tuz; Podder, Priyanka; Alam, Rayhan; Hasnat, Md Abul; Biman, Tanvir Ahmed; Sultana, Tania; Reza, Md Selim (Bangladesh Journal of Nuclear Medicine, 2026)
Objective: To evaluate the metabolic and anatomical characteristics of brain malignancies using 18F-FDG PET-CT, with emphasis on diagnostic and clinical relevance. Methods: A retrospective analysis of 2,879 FDG PET-CT scans performed between January 2019 and December 2023 at the Institute of Nuclear Medical Physics (INMP), Savar. Parameters assessed included lesion metabolic activity (SUVmax), anatomical localization, CT appearance, and correlation with histopathological diagnosis. Results: Seventeen patients were identified with malignant brain lesions. Among them, three were primary gliomas, two were primary CNS lymphomas, and twelve were metastatic lesions—originating from breast (n = 4), lung (n = 3), carcinoma of unknown origin (n = 3), prostate (n = 1), and tongue (n = 1). High-grade gliomas exhibited markedly elevated SUVmax values. Conclusion: FDG PET-CT delineated tumor margins and multifocal disease accurately, complementing MRI by providing essential metabolic data for staging and treatment planning. Further prospective studies are recommended to define its prognostic utility. Bangladesh J. Nuclear Med. 29(1): 43-49, 2026